EXTRACTION OF GRAPE SEED BY SUPERCRITICAL CARBON DIOXIDE - Akgun, Nalan; Akgun, Mesut (YILDIZ TECHNICAL UNIV, 2006)
Supercritical fluid extraction of grape seed oil was performed to study the effect of various parameters such as pressure (80-120 bar), temperature (40-50 degrees C) and modifier concentration (10-30%) on the yield and composition of oil. Experiments were performed based on experimental design in three levels. The maximum yield of the oil was obtained by adding 30% of methanol as a modifier. The fatty acid composition of grape seed oil was analyzed by GC-MS using by a standard estimation method. Unsaturated fatty acids constitute about 70% of the oil, in conformance with respective literature.
Keywords: Grape pomace; supercritical fluid extraction; winery by-products; grape seed oil; FLUID EXTRACTION; HIGH-PRESSURE; SOLUBILITY; ETHANOL; YIELD; ACIDS; OILS; Engineering